A preparation method of monoclinal phase nano zirconium oxide
Patent Information
- Application Number
- CN202510527153.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
AI Technical Summary
该制备方法原料繁琐,需分别配制不同浓度溶液,过程中对浓度把控要求高,操作复杂
[0020]1、本发明提供的一种可批量生产单斜相纳米氧化锆的制备方法,通过制备固液混合的前驱体,经旋转蒸发操作,使前驱体中的液相溶剂能够在相对较低温度快速蒸发出来,同时较低水浴温度有利于前驱体中固相颗粒的缓慢成核生长,并通过旋蒸过程使前驱体不断在茄形瓶中挂壁形成一层固液膜,使得固体结晶过程不断被破坏,颗粒来不及充分生长和聚集,从而得到粒径细小的前驱体晶粒,最终实现纳米氧化锆材料的制备。
Smart Images

Figure CN122977840A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic material preparation technology, specifically relating to a method for mass-producing monoclinic phase nano-zirconia. Background Technology
[0002] Monoclinic zirconia, as an important crystal form of zirconia, exhibits excellent high-temperature resistance, capable of withstanding extremely high-temperature environments and maintaining its structural integrity even under extreme thermal shock. Its hardness is also outstanding, possessing a high Mohs hardness, giving it excellent wear resistance and effectively resisting external mechanical friction and corrosion. In terms of thermal properties, its low thermal conductivity makes it highly promising for applications in thermal insulation. Chemically, monoclinic zirconia is extremely stable, maintaining good resistance to acid and alkali corrosion in both strongly oxidizing and strongly reducing atmospheres, and is not easily reacted with common chemical substances. Particularly noteworthy is its excellent biocompatibility, which broadens its application prospects in the biomedical field.
[0003] In the ceramics industry, monoclinic zirconia, as a key additive, can significantly improve the mechanical properties of ceramic materials, enhancing their strength and toughness, thereby enabling the production of high-performance structural and functional ceramics for applications in high-end fields such as aerospace and machinery manufacturing. In the field of special refractory materials, the high-temperature resistance, thermal shock resistance, and corrosion resistance of monoclinic zirconia make it an ideal raw material for manufacturing high-performance refractory materials.
[0004] However, in actual preparation processes, it is often difficult to completely avoid the formation of other crystal forms. Especially when the temperature variation range is large or the reaction time is not precisely controlled, tetragonal or cubic zirconia may appear as impurities. The presence of these impurity phases will seriously affect the performance consistency and stability of monoclinic zirconia materials.
[0005] Chinese patent CN119143175A, entitled "A Monoclinic Zirconia Nanopowder and Its Preparation Method and Application," discloses a monoclinic zirconia nanopowder, its preparation method, and its application. The method involves dissolving zirconium oxychloride octahydrate in water and placing it in a hydrothermal reactor. The mixture is then reacted at 140-160℃ for 12-16 hours, followed by cooling and settling to precipitate. Ammonia is then added for ammonolysis and aging. The precipitate is separated, washed, and dried to obtain a zirconium hydroxide precursor. Finally, the precursor is calcined in air at 850-950℃ to obtain the final product. However, this preparation method involves an ammonolysis reaction, which is difficult to control. The concentration and amount of ammonia, as well as the reaction time, significantly affect the precipitation effect and product quality. Improper control can easily lead to incomplete zirconium ion precipitation or uneven particle size distribution, affecting the final product performance.
[0006] Chinese patent CN117263240A, entitled "A Method for Preparing Monoclinic Zirconia Powder and Monoclinic Zirconia Powder," discloses a method for preparing monoclinic zirconia powder and the resulting powder. The method involves preparing a solution of water-soluble zirconium salt and a dispersant, then simultaneously adding the solution and urea solution dropwise into a reaction vessel to obtain a precipitate. This precipitate is first washed with dilute ammonia, then washed with water until chloride ions are removed. The precipitate is then calcined at 550-750℃ for 2-5 hours to obtain monoclinic zirconia. This preparation method requires washing with dilute ammonia, which is time-consuming, produces a strong odor from the volatile ammonia, and is pungent, making it unfriendly to operators and the environment.
[0007] Chinese patent CN111573728B, entitled "Pure Monoclinic Phase Nanoscale Zirconia Powder with Ultra-High Specific Surface Area and Preparation Method Thereof," discloses a method for preparing pure monoclinic phase nanoscale zirconium dioxide powder with ultra-high specific surface area. The method involves preparing solution A by stirring and ultrasonically mixing water-soluble zirconium salt, and then preparing a NaOH solution B of the same concentration. A dispersant is mixed with water, and solution B is added to adjust the pH to 10. Solutions A and B are then added to adjust the pH to 7-7.5, and finally solution B is added again to adjust the pH to 9-10, resulting in slurry C. Slurry C is washed with deionized water, dried, and calcined to obtain calcined powder. The calcined powder is ball-milled with water, filtered, dried, ground, and sieved to obtain the final product. This preparation method involves cumbersome raw materials, requires the preparation of solutions of different concentrations, and demands high precision in concentration control during the process, making the operation complex. Summary of the Invention
[0008] To address the problems existing in the prior art, the present invention aims to provide a method for preparing monoclinic phase nano-zirconia with a stable mass production process. This preparation process is simple, low-cost, and produces monoclinic phase zirconia ceramic powder that is non-toxic, harmless, high-purity, ultrafine, and has a uniform and controllable composition.
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] A method for mass-producing monoclinic phase nano-zirconia specifically includes the following steps:
[0011] Step 1: Weigh zirconium oxychloride and fructose, place them in a beaker and add deionized water, stir to obtain a white solution, which is the zirconium oxide precursor solution;
[0012] Step 2: Transfer the zirconia precursor solution obtained in Step 1 into a flask and allow it to undergo a rotary evaporation reaction. After centrifugation and washing, place it in an oven to dry and obtain zirconia precursor powder.
[0013] Step 3: Place the zirconia precursor powder obtained in Step 2 into a muffle furnace and calcine it at high temperature in air to obtain monoclinic zirconia nanoparticles.
[0014] Furthermore, the molar ratio of zirconium oxychloride to fructose in step 1 is 1:2.
[0015] Furthermore, the stirring process in step 1 is carried out using a magnetic stirrer, and the stirring time is 30-60 minutes.
[0016] Furthermore, the specific steps for step 2 are as follows:
[0017] The zirconia precursor solution obtained in step 1 was transferred into a flask and subjected to rotary evaporation. The rotary evaporation conditions were as follows: initially, rotary evaporation was carried out at 78 mbar and 60 °C, and the pressure was gradually reduced while the temperature was increased, eventually stopping at 72 mbar and 70 °C, with the rotary evaporation lasting for 30-60 min. Then, centrifugation and washing were performed, first washing three times with deionized water, and then washing three times with anhydrous ethanol. Finally, the solution was placed in an oven at 80 °C and dried for 24-48 h to obtain zirconia precursor powder.
[0018] Furthermore, in step 3, the high-temperature calcination temperature is 1000℃, and the holding time is 120-180min.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] 1. The present invention provides a method for mass-producing monoclinic phase nano-zirconia. By preparing a solid-liquid mixed precursor, the liquid solvent in the precursor can be rapidly evaporated at a relatively low temperature through rotary evaporation. At the same time, the low water bath temperature is conducive to the slow nucleation and growth of solid particles in the precursor. Through the rotary evaporation process, the precursor continuously forms a solid-liquid film on the wall of the flask, which continuously disrupts the solid crystallization process and prevents the particles from growing and aggregating sufficiently, thereby obtaining precursor grains with fine particle size, and finally realizing the preparation of nano-zirconia materials.
[0021] 2. This invention provides a method for mass-producing monoclinic phase nano-zirconia. The method avoids the use of ammonia during preparation, selects food-grade fructose as a chelating agent, and the reaction process is non-toxic, odorless, and under mild conditions. Fructose binds to Zr through coordination. 4+ The formation of stable complexes effectively slows down the hydrolysis rate and avoids rapid nucleation caused by local supersaturation in the reaction system, thereby controlling the nucleation and growth process of particles and ultimately obtaining smaller and more uniformly distributed nanoparticles. At the same time, it reduces the aggregation phenomenon between particles, laying the foundation for the mass production of high-quality, process-stable monoclinic phase nano-zirconia.
[0022] 3. The raw materials used in this preparation method are low-cost, readily available, and easy to implement with good repeatability. The reaction process is mild and pollution-free, making it suitable for large-scale production and with broad application prospects. Attached Figure Description
[0023] Figure 1A process flow diagram of a method for preparing monoclinic phase nano-zirconia that can be mass-produced according to the present invention;
[0024] Figure 2 To calculate the ammonia (NH3·H2O) and fructose (C6H2O) separately using HSC software 12 Schematic diagram of the Gibbs free energy ΔG of the reaction after the addition of O6;
[0025] Figure 3 The X-ray diffraction patterns of the monoclinic zirconia nanomaterials prepared in Examples 1-3 of this invention are shown below.
[0026] Figure 4 These are scanning electron microscope (SEM) images of the monoclinic zirconia nanomaterials prepared in Examples 1-3 of this invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] like Figure 1 As shown, a method for mass-producing monoclinic phase nano-zirconia is described, with the following specific steps:
[0029] Step 1, Prepare the precursor solution: Add zirconium oxychloride (ZrOCl2) and fructose (C6H2O) to the solution. 12 Weigh out O6 at a molar ratio of 1:2, place it in a beaker, add deionized water, and stir to obtain a white solution, which is the zirconium oxide precursor solution. The stirring process is carried out using a magnetic stirrer, and the stirring time is 30-60 minutes.
[0030] Step 2, preparation of precursor powder by rotary evaporation: The zirconia precursor solution obtained in Step 1 was transferred into a flask. Initially, rotary evaporation was carried out at 78 mbar and 60 °C. The pressure was gradually reduced and the temperature was increased, eventually stopping at 72 mbar and 70 °C. Rotary evaporation was carried out for 30-60 min. Then, centrifugation and washing were performed. During centrifugation and washing, the sample was first washed 3 times with deionized water and then 3 times with anhydrous ethanol. Finally, the sample was placed in an oven at 80 °C and dried for 24-48 h to obtain zirconia precursor powder.
[0031] Step 3, high-temperature sintering to prepare zirconia nanomaterials: The zirconia precursor powder obtained in step 2 is placed in a muffle furnace and calcined at high temperature in air. The high-temperature calcination temperature is 1000℃ and the holding time is 120-180min to obtain monoclinic zirconia nanoparticles.
[0032] Example 1
[0033] Step 1, Prepare the precursor solution: Weigh 16.275g ZrOCl2 and 18.198g C6H 12 Place O6 in a beaker and add 50 mL of deionized water. Stir with a magnetic stirrer for 30 min to obtain the zirconium oxide precursor solution.
[0034] Step 2, preparation of precursor powder by rotary evaporation: The zirconia precursor solution obtained in Step 1 was transferred into a flask. Initially, rotary evaporation was carried out at 78 mbar and 60 °C. The pressure was gradually reduced and the temperature was increased, and finally stopped at 72 mbar and 70 °C. The rotary evaporation lasted for 30 min. During centrifugation and washing, the sample was first washed 3 times with deionized water and then 3 times with anhydrous ethanol. Finally, the sample was placed in an oven at 80 °C and dried for 24 h to obtain zirconia precursor powder.
[0035] Step 3, high-temperature sintering to prepare zirconia nanomaterials: The zirconia precursor powder obtained in step 2 is placed in a muffle furnace and calcined at high temperature in air. The high-temperature calcination temperature is 1000℃ and the holding time is 120min to obtain monoclinic zirconia nanoparticles.
[0036] Example 2
[0037] Step 1, Prepare the precursor solution: Weigh 162.75g ZrOCl2 and 181.98g C6H 12 Place O6 in a beaker and add 500 mL of deionized water. Stir with a magnetic stirrer for 30 minutes to obtain the zirconium oxide precursor solution.
[0038] Step 2, preparation of precursor powder by rotary evaporation: The zirconia precursor solution obtained in Step 1 was transferred into a round-bottom flask. Initially, rotary evaporation was carried out at 78 mbar and 60 °C, gradually reducing the pressure and increasing the temperature, eventually stopping at 72 mbar and 70 °C. Rotary evaporation continued for 30 min. During centrifugation and washing, the sample was first washed three times with deionized water, then three times with anhydrous ethanol. Finally, it was dried in an oven at 80 °C for 24 h to obtain zirconia precursor powder.
[0039] Step 3, high-temperature sintering to prepare zirconia nanomaterials: The zirconia precursor powder obtained in step 2 is placed in a muffle furnace and calcined at high temperature in air at 1000℃ for 120 min to obtain monoclinic zirconia nanoparticles.
[0040] Example 3
[0041] Step 1, Prepare the precursor solution: Weigh 1627.5g ZrOCl2 and 1819.8g C6H 12Place O6 in a beaker and add 5000 mL of deionized water. Stir with a magnetic stirrer for 60 min to obtain the zirconium oxide precursor solution.
[0042] Step 2, preparation of precursor powder by rotary evaporation: The zirconia precursor solution obtained in Step 1 was transferred into a round-bottom flask. Initially, rotary evaporation was carried out at 78 mbar and 60 °C, gradually reducing the pressure and increasing the temperature, eventually stopping at 72 mbar and 70 °C. Rotary evaporation continued for 60 min. During centrifugation and washing, the sample was first washed three times with deionized water, then three times with anhydrous ethanol. Finally, it was dried in an oven at 80 °C for 48 h to obtain zirconia precursor powder.
[0043] Step 3, high-temperature sintering to prepare zirconia nanomaterials: The zirconia precursor powder obtained in step 2 is placed in a muffle furnace and calcined at high temperature in air at 1000℃ for 180 min to obtain monoclinic zirconia nanoparticles.
[0044] The ammonia (NH3·H2O) and fructose (C6H2O) were calculated using HSC software. 12 The Gibbs free energy ΔG of the reaction after the addition of O6 is as follows: Figure 2 As shown, from Figure 2 As can be seen from this, compared to ammonia (NH3·H2O), the addition of fructose (C6H2O) is more effective. 12 When O6 is used as a chelating agent, the Gibbs free energy of the reaction is lower, indicating that the reaction proceeds more readily under thermodynamic conditions after the addition of fructose. The following are the chemical equations for the two reactions:
[0045] 4NH3·H2O+2ZrOCl2+7O2=2ZrO2+8H2O+4HCl+4NO2
[0046] 2C6H 12 O6+ZrOCl2+12O2=ZrO2+11H2O+12CO2+2HCl
[0047] X-ray diffraction (XRD) analysis was performed on the monoclinic phase nano-zirconia prepared in Examples 1-3 of this invention, as follows: Figure 3 As shown, from Figure 3 The results show that the characteristic peaks of monoclinic zirconia appear in the nanomaterials and correspond to their standard cards. The prepared monoclinic zirconia nanomaterials have good crystallinity and are basically free of impurity phases. Therefore, it can be concluded that the method of this invention can be used to prepare stable monoclinic zirconia nanomaterials in batches.
[0048] The morphology of the monoclinic phase zirconia nanomaterials prepared in Examples 1-3 of this invention was analyzed using scanning electron microscopy (SEM), such as... Figure 4 As shown, where Figure 4(a1)-(a3) are photographs taken at magnifications of 10,000x, 50,000x, and 100,000x respectively for the nano-zirconia prepared in Example 1. Figure 4 (a1) exhibits a large blocky structure with irregular edges. Figure 4 (a2) and Figure 4 (a3) The particles can be seen to be polygonal and tightly packed; Figure 4 (b1)-(b3), Figure 4 (c1)-(c3) are photographs taken at magnifications of 10,000x, 50,000x, and 100,000x respectively for the nano-zirconia nanoparticles prepared in Examples 2 and 3. The particle size is basically the same as that in Example 1. By comparing the three sets of examples, it can be seen that the zirconia nanoparticles are uniformly distributed with an average particle size of 35 nm, proving that the method of the present invention can successfully prepare high-purity, ultrafine, and uniformly controllable zirconia nanomaterials.
[0049] The ceramic yield and precursor conversion rate of monoclinic phase nano-zirconia prepared in Examples 1-3 were obtained by calculation, as shown in Table 1. It can be seen that after scaling up the system, the ceramic yield and precursor conversion rate are not much different, indicating that the method of the present invention has good repeatability and is suitable for mass production.
[0050] Table 1
[0051]
[0052] The grain size of monoclinic nano-zirconia prepared in Examples 1-3 was calculated using the Scherrer formula, as shown in Table 2. It can be seen that the zirconia grain size prepared in different systems is between 30-35 nm, indicating that the method of the present invention successfully controls the grain growth process.
[0053] Table 2
[0054]
[0055] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing monoclinic phase nano-zirconia for mass production, characterized in that, Specifically, the following steps are included: Step 1: Weigh zirconium oxychloride and fructose, place them in a beaker and add deionized water, stir to obtain a white solution, which is the zirconium oxide precursor solution; Step 2: Transfer the zirconia precursor solution obtained in Step 1 into a flask and allow it to undergo a rotary evaporation reaction. After centrifugation and washing, place it in an oven to dry and obtain zirconia precursor powder. Step 3: Place the zirconia precursor powder obtained in Step 2 into a muffle furnace and calcine it at high temperature in air to obtain monoclinic zirconia nanoparticles.
2. The method for preparing monoclinic phase nano-zirconia in mass production according to claim 1, characterized in that, The molar ratio of zirconium oxychloride to fructose in step 1 is 1:
2.
3. The method for preparing monoclinic phase nano-zirconia in mass production according to claim 1, characterized in that, The mixing process in step 1 is carried out using a magnetic stirrer, and the mixing time is 30-60 minutes.
4. The method for preparing monoclinic phase nano-zirconia in mass production according to claim 1, characterized in that, The specific steps for step 2 are as follows: The zirconia precursor solution obtained in step 1 was transferred into a flask and subjected to rotary evaporation. The rotary evaporation conditions were as follows: initially, rotary evaporation was carried out at 78 mbar and 60 °C, and the pressure was gradually reduced while the temperature was increased, eventually stopping at 72 mbar and 70 °C, with the rotary evaporation lasting for 30-60 min. Then, centrifugation and washing were performed, first washing three times with deionized water, and then washing three times with anhydrous ethanol. Finally, the solution was placed in an oven at 80 °C and dried for 24-48 h to obtain zirconia precursor powder.
5. The method for preparing monoclinic phase nano-zirconia in mass production according to claim 1, characterized in that, In step 3, the high-temperature calcination temperature is 1000℃, and the holding time is 120-180min.
Citation Information
Patent Citations
Ultra-high specific surface area pure monoclinic phase nanoscale zirconium dioxide powder and its preparation method
CN111573728B
Preparation method of monoclinic phase zirconium oxide powder and monoclinic phase zirconium oxide powder
CN117263240A
Monoclinic phase zirconium oxide nano powder as well as preparation method and application thereof
CN119143175A